Simulating the breakage of glass under hard body impact using the combined finite-discrete element method. (December 2016) - Chen, Xudong; Chan, Andrew H.C.; Yang, Jian
Highlights: 2D & 3D Impact fracture & fragmentation of glass was modelled using the FEM-DEM. A combined single and smeared crack model was used. Results are validated with existing numerical simulations and experiments. Glass impact breakage mechanism, fracture regimes and thresholds are established. Abstract: The fracture behaviour of glass under hard body impact is simulated using the combined finite-discrete element method with a finite element incorporated into the discrete elements. A Mode I fracture model is employed and proven to be successful in modelling the crack initiation and tracking the crack propagation in glass. Cone, flexural and punching damages are obtained thus qualitatively verified the glass fracture model. A parametric study on tensile strength, fracture energy and impact velocity further examines the breakage behaviour of glass, demonstrating the applicability of this computational technique for the analysis of glass impact mechanism.